(3cGTaI GdZeI Yf MUf SjQI EeGe GdCFeI CejQ GdeDefjf UdGM GdOjf GdfGUQ dOjf Gddgs - (3GdgGOj Hf EHQGgje Hf Ydj Hf GdeQJVj GdMSjfj Hf GdhRjQ,LeGd GdOjf , GHf GdhRjQ, J (B822 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi aJb Yf bdhH ChdjGFg CZTjI hhab NhGWQ CfHjGFg dELJfGA KeQGJ GdMceI s
(3BNQgG (B:s
(3hEfgG PQGFY Edi GdQVhGf GdCcHQ , heYGQL Edi GdXaQ HGdKhGH GdChai HMb eMeO hBdg Ke GdcJGH Hef Gddg s
(3GdfSNI HgG MhGTs
(3cJHJ GdYfhGJ HNW eLhOs
(3Ydi MhGTjgG HYV GdTQhM GdeajOI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs